PEMBINAAN AL-QUR’AN DAN HADIS TK/TPA DESA TOMPONG PATU KECAMATAN KAHU KABUPATEN BONE - Ardillah,; Ikbal, Muh.; Hamzah, Amir; Firdaus; Arif Ahmad Marzuki, Mudzakkir Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2023)
Coaching is defined as educational efforts both formal and non-formal that are carried out consciously, planned, directed, and are responsible for growing, guiding, and developing the basics of personality, knowledge, and skills that are balanced, whole, and harmonious. Talents and abilities possessed as provisions to add, improve and develop themselves, fellow human beings and the environment towards achieving human beings who are dignified, have quality and ability and an independent personality. This activity aims to improve the memorization of short letters and develop knowledge in reading the Qur'an for students, and is expected to play a major role in teaching the ability to read and write the Qur'an as well as strongly support the development of the child's soul as knowledge of worship, faith, and morals considering that the material taught is not only focused on reading and writing the Qur'an but also provides material on worship, faith and morals which aims to prepare students to become Qur'anic people and make the Qur'an a guide in his life.